Réponses

Meilleure réponse !
2014-06-08T08:56:48+02:00
Bonjour,

(sec^2\theta+cosec^2\theta)\times\sin^2\theta\\\\=(\dfrac{1}{\cos^2\theta}+\dfrac{1}{\sin^2\theta})\times\sin^2\theta}\\\\=(\dfrac{\sin^2\theta}{\sin^2\theta\cos^2\theta}+\dfrac{\cos^2\theta}{\sin^2\theta\cos^2\theta})\times\sin^2\theta}\\\\=(\dfrac{\sin^2\theta+\cos^2\theta}{\sin^2\theta\cos^2\theta})\times\sin^2\theta}\\\\=(\dfrac{1}{\sin^2\theta\cos^2\theta})\times\sin^2\theta}\\\\=\dfrac{\sin^2\theta}{\sin^2\theta\cos^2\theta}

\\\\=\boxed{\dfrac{1}{\cos^2\theta}}\\\\=\boxed{sec^2\theta}
je ne voie pas toute ta rwponse
C'est étonnant puisque je la vois sous mes yeux... :)
peut parce que jai laplication